2007
DOI: 10.1002/gcc.20512
|View full text |Cite
|
Sign up to set email alerts
|

Arylamine N‐acetyltransferase 1 expression in breast cancer cell lines: A potential marker in estrogen receptor‐positive tumors

Abstract: The prognosis for patients with estrogen receptor (ER)-positive breast cancer has improved significantly with the prescription of selective ER modulators (SERMs) for ER-positive breast cancer treatment. However, only a proportion of ER-positive tumors respond to SERMs, and resistance to hormonal therapies is still a major problem. Detailed analysis of published microarray studies revealed a positive correlation between overexpression of the drug metabolizing enzyme arylamine N-acetyltransferase type 1 (NAT1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
65
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 45 publications
4
65
0
Order By: Relevance
“…Several studies have shown higher mRNA and protein expression of NAT1 in ER-positive breast cancer compared with the expression in ER-negative disease (Perou et al 2000, Adam et al 2003, Tozlu et al 2006, Wakefield et al 2008. Moreover, it was reported that high expression of NAT1 was correlated with better outcome in ER-positive breast cancer (Bieche et al 2004, Dolled-Filhart et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown higher mRNA and protein expression of NAT1 in ER-positive breast cancer compared with the expression in ER-negative disease (Perou et al 2000, Adam et al 2003, Tozlu et al 2006, Wakefield et al 2008. Moreover, it was reported that high expression of NAT1 was correlated with better outcome in ER-positive breast cancer (Bieche et al 2004, Dolled-Filhart et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several nonsubstrates such as tamoxifen (Lee et al, 1997) and cisplatin (Ragunathan et al, 2008) are known to down-regulate its activity. It is noteworthy that the latter are commonly used as antitumor agents, and recent data suggest that cisplatin-induced NAT1 inactivation contributes to their beneficial effects, not least because of increasing evidence for a dysregulation of NAT1 in certain cancer cells (Adam et al, 2003;Wakefield et al, 2008).…”
mentioning
confidence: 99%
“…Also, if our findings can be applied to tissues other than the liver-e.g., breast or prostate, where (HUMAN)NAT1 has been shown to highly contribute to tumor malignancy-concerns should arise about the administration of glucocorticoids to cancer patients. In this context, it should be noted that Wakefield et al (6) showed that among different ER + breast cancer cell lines, only those with the highest NAT1 activity (ZR-75-1) had NAT1 transcripts originating from P3, suggesting the inducibility/activation of this promoter and potential pertinence of our findings to tissues are different from the liver. The recurrent prescription of glucocorticoids as cancer co-treatment (42) could thus exacerbate cancer malignancy, due to the increasing evidence of (HUMAN)NAT1 overexpression and its contribution to tumor initiation and progression.…”
Section: Discussionmentioning
confidence: 64%
“…It was also shown that the (HUMAN)NAT1 gene was down-regulated in late-stage breast cancer (6). In addition, DNA hypomethylation in the (HU-MAN)NAT1 gene was reported in cancerous breast tissues (7).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation